LncRNA HOTAIR: A Novel Biomarker for the Diagnosis of Asymptomatic Carotid Artery Stenosis and Prediction of the Onset of Cerebral Ischemic Events - Pengcheng Feng; Chenguang Tong; Yuan Li; Li Liu (Artery Research)
Abstract Background Carotid artery stenosis (CAS) is a major cause of cerebral ischemic events (CIE). The purpose of the research was to reveal the diagnostic accuracy of long non-coding RNA hox transcript antisense intergenic RNA (HOTAIR) in asymptomatic carotid artery stenosis (ACAS) patients and its predictive significance in CIE incidence. Methods 88 patients with ACAS and 80 controls were included. Blood samples were collected and serum HOTAIR levels were detected by qRT-PCR. Logistic regression examined factors associated with the degree of carotid stenosis. The receiver operating characteristic (ROC) curve assessed the diagnostic accuracy of HOTAIR in identifying patients with ACAS. Predictive value of serum HOTAIR levels for the occurrence of CIE was assessed by Kaplan–Meier curves and Cox regression. Results Serum HOTAIR was markedly lower in ACAS patients than in controls (P < 0.001). Logistic regressions confirmed that HOTAIR levels correlated with severe carotid artery stenosis (OR = 0.289, 95% CI = 0.107–0.786, P = 0.015). ROC’s AUC was 0.925, indicating high sensitivity and specificity in differentiating between the controls and patients with ACAS. Furthermore, CIE-positive patients had lower HOTAIR levels than CIE-negative, and the degree of carotid stenosis (HR = 4.566, 95% CI = 1.206–17.292, P = 0.025) and HOTAIR levels (HR = 0.244, 95% CI = 0.072–0.824, P = 0.023) were independent risk factors for the development of CIE. Patients with lower HOTAIR were more susceptible to CIE (log-rank P = 0.001). Conclusions Serum HOTAIR was reduced in patients with ACAS and may be a non-invasive diagnostic biomarker for ACAS and predicts the development of CIE.